Preventive effect of surface charge on encrustation of biodegradable ureteral stents. Issue 2 (22nd January 2023) - Li, Kaiqi; Liu, Xiliang; Fan, Youkun; Feng, Shaomin; Chen, Dongliang
Abstract: Prevention of encrustation on the surface has always been the biggest challenge for urological implants. In the field of ureteral stent design, biodegradability has attracted much attention in recent years, because biodegradable ureteral stents not only avoid secondary intervention, but also prevent encrustation due to surface renewal by degradation process. Furthermore, researches have focus on some surface parameters to provide guidance for the development of stent materials, such as hydrophilicity or surface charge. In this work, we synthesized two types of poly(ester-carbonate)s, poly(L-lactide-co-5-amino-1, 3-dioxan-2-one) (P(LA-co-AC)) containing amino, and poly (L-lactide-co-5-methyl-5-carboxyl-1, 3-dioxan-2-one) (P(LA-co-MCC)) containing carboxyl. Blending P(LA-co-AC) and P(LA-co-MCC) with poly(L-lactide-co-Ɛ-caprolactone) (PLACL) respectively, two types of ureteral stent materials were prepared. Due to the influence of ions formed by the dissociation of amino and carboxyl, two types of materials show differences in surface charge analyses. We further developed a dynamic urinary extracorporeal circulation (DUEC) system to assess in vitro encrustation of materials with different surface charges. The results of this comparative study identified that the materials with strong negative surface charge were most favorable for use as ureteral stent, and provided a new approach to surmount the problems faced by urological surgery which complied with the future trend of biodegradable ureteral stent design.